2021
DOI: 10.3390/children8040302
|View full text |Cite
|
Sign up to set email alerts
|

The Most Common Vitamin D Receptor Polymorphisms (ApaI,FokI, TaqI, BsmI, and BglI) in Children with Dental Caries: A Systematic Review and Meta-Analysis

Abstract: Vitamin D participates in the calcification of enamel and dentin and the appropriate immune responses to oral microbial infections. We aimed to assess the association between the most common vitamin D receptor (VDR) polymorphisms (ApaI,FokI, TaqI, BsmI, and BglI) and the risk of dental caries in children. Methods: PubMed/MEDLINE, Cochrane Library, Web of Science, and Scopus databases were comprehensively searched until 19 January 2021. Meta-analysis with odds ratios as the effect estimate along with 95% confid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 50 publications
(26 reference statements)
3
14
0
Order By: Relevance
“…The results of meta-analysis of allelic, recessive, dominant, and overdominant models at rs739837, rs2228570, and rs7975232 revealed no signi cant differences in genotype distributions between the caries and caries-free groups, consistent with the ndings of Sadeghi et al [43] ,…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The results of meta-analysis of allelic, recessive, dominant, and overdominant models at rs739837, rs2228570, and rs7975232 revealed no signi cant differences in genotype distributions between the caries and caries-free groups, consistent with the ndings of Sadeghi et al [43] ,…”
Section: Discussionsupporting
confidence: 88%
“…Sadeghi et al [43] named genotypes at this locus based on restriction of endonuclease digestion sites. After one-to-one comparison, the results of this study were consistent with those of Sadeghi et al [43] . The reason why rs10735810 is associated with susceptibility to caries may be related to the interaction of its cotranscription factors and its location in the gene structure [46] ; rs10735810 is located near the 5'untranslated region of the VDR gene, within the DNA binding domain [47][48][49][50] , and the polymorphism changes the rst potential start codon of the VDR gene, from ATG to ACG, resulting in a VDR protein truncated by three amino acids, which is more effective in transactivation of vitamin D target genes [51] .…”
Section: Discussionmentioning
confidence: 99%
“…disorders (Yildiz et al, 2021), and the Bb (AG) and bb (GG) genotypes are associated with caries risk in children (Kong et al, 2017;Sadeghi et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…As a result, optimum vitamin D3 levels in children are required as a secondary preventive intervention for dental cavities in the permanent dentition [ 26 ]. Another study concluded that among the vitamin D3 receptor polymorphisms studied, a relation was found between the FokI polymorphism (rs10735810) and the risk of dental caries, with the protective effect of the f allele and ff genotype [ 27 ].…”
Section: Discussionmentioning
confidence: 99%